The Power of Movement in Plants - Darwin, Charles, 1809-1882; Darwin, Francis, Sir, 1848-1925 (Salt Lake City, UT : Project Gutenberg, 2004)
"The Power of Movement in Plants" by Charles Darwin, assisted by Francis Darwin, is a scientific publication written in the late 19th century. This work delves into the intricate movements of various plant parts, specifically focusing on how they adapt and respond to their environment through mechanisms such as circumnutation and geotropism, which illustrate the complexity of plant behavior often compared to animal movement. The opening of the book provides a detailed introduction to the concept of circumnutation$1 (Bthe circular or spiral movements made by the tips of plants during growth. Darwin explains the various conditions under which these movements can be observed, and he introduces specific plant examples. In the first chapter, he begins with the circumnutating movements of seedlings, describing experiments involving the radicles, hypocotyls, and cotyledons of Brassica oleracea and other species. Through observations and detailed descriptions of their movements, Darwin lays the groundwork for understanding the mechanisms governing plant movement and responses to stimuli such as gravity and light. This detailed examination sets the stage for the subsequent chapters, which will explore similar characteristics in various plants. (This is an automatically generated summary.)s
Release date is 2004-05-01
Sue Asscher
Keywords: Botany; Plants -- Irritability and movements; Geotropism